SIPL1, Regulated by MAZ, Promotes Tumor Progression and Predicts Poor Survival in Human Triple-Negative Breast Cancer - He, Juanjuan; Wang, Jing; Li, Teng; Chen, Kunlun; Li, Songchao; Zhang, Shaojin (Frontiers in Oncology, 2021)
Background Triple-negative breast cancer (TNBC) is an aggressive subtype of breast cancer owing to a lack of effective targeted therapy and acquired chemoresistance. Here, we explored the function and mechanism of shank-interacting protein-like 1 (SIPL1) in TNBC progression. Methods SIPL1 expression was examined in human TNBC tissues and cell lines by quantitative reverse transcription PCR, western blot, and immunohistochemistry. SIPL1 overexpression and silenced cell lines were established in BT549 and MDA-MB231 cells. The biological functions of SIPL1 in TNBC were studied in vitro using the CCK-8 assay, CellTiter-Glo Luminescent Cell Viability assay, caspase-3/8/9 assay, wound healing assay, and transwell assay and in vivo using a nude mouse model. The potential mechanisms underlying the effects of SIPL1 on TNBC progression were explored using bioinformatics analysis, luciferase reporter assays, and chromatin immunoprecipitation followed by qPCR. Results SIPL1 expression was higher in human TNBC tissues and cell lines than in adjacent normal tissues and a breast epithelial cell line (MCF10A). High expression of SIPL1 was positively correlated with poor overall and disease-free survival in patients with TNBC. SIPL1 overexpression elevated and SIPL1 silencing repressed the malignant phenotypes of TNBC cells in vitro. SIPL1 overexpression promoted xenograft tumor growth in vivo. Myc-associated zinc-finger protein (MAZ) transcriptionally activated SIPL1. Finally, we found that SIPL1 promoted TNBC malignant phenotypes via activation of the AKT/NF-κB signaling pathways. Conclusions These results indicate that the MAZ/SIPL1/AKT/NF-κB axis plays a crucial role in promoting the malignant phenotypes of TNBC cells.